2013
DOI: 10.1182/blood-2012-09-456780
|View full text |Cite
|
Sign up to set email alerts
|

Preferential HLA-DRB1*11–dependent presentation of CUB2-derived peptides by ADAMTS13-pulsed dendritic cells

Abstract: Key Points• ADAMTS13 derived peptides presented on HLA-DR; implications for acquired TTP.• CUB2 domain peptide binds to risk-allele HLA-DRB1*11.Autoantibodies directed against ADAMTS13 prohibit the processing of von Willebrand factor multimers, initiating a rare and life-threatening disorder called acquired thrombotic thrombocytopenic purpura (TTP). Recently, HLA-DRB1*11 has been identified as a risk factor for the development of acquired TTP. Here, we identified ADAMTS13-derived peptides presented on MHC clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 41 publications
(77 reference statements)
2
47
0
2
Order By: Relevance
“…17 These findings reveal a critical role for DCs in the initiation of CD4 1 T-cell responses to ADAMTS13 in patients with acquired TTP.…”
mentioning
confidence: 94%
“…17 These findings reveal a critical role for DCs in the initiation of CD4 1 T-cell responses to ADAMTS13 in patients with acquired TTP.…”
mentioning
confidence: 94%
“…Several studies have shown that protein glycans may be crucial also for T-cell recognition of autoantigens in autoimmune disorders [10]. Previously we have shown that antigen presenting cells derived from HLA-DRB1*11-positive individuals present a CUB2 domain derived peptide FINVAPHARIA (residues 1327-1338) [27]. Since HLA-DRB1*11 is considered to be a risk factor for the development of acquired TTP [28][29][30] functional presentation of this CUB2 domain-derived peptide might contribute to the onset of acquired TTP [27].…”
Section: Discussionmentioning
confidence: 97%
“…Previously we have shown that antigen presenting cells derived from HLA-DRB1*11-positive individuals present a CUB2 domain derived peptide FINVAPHARIA (residues 1327-1338) [27]. Since HLA-DRB1*11 is considered to be a risk factor for the development of acquired TTP [28][29][30] functional presentation of this CUB2 domain-derived peptide might contribute to the onset of acquired TTP [27]. Presentation of the FINVAPHARIA peptide (residues 1327-1338) may potentially be affected by the presence of an N-linked glycan at N1354.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] We have explored the repertoire of ADAMTS13 peptides presented on major histocompatibility complex class II (MHC-II). 12 Pulsing of dendritic cells from healthy donors showed preferential presentation of the CUB2 domain-derived peptide FINVAPHAR on HLA-DRB1*11. 12 In addition, we observed presentation of a CUB2 domain peptide with the core sequence ASYILIRD on antigen-presenting cells derived from HLA-DRB1*03-positive individuals.…”
Section: Introductionmentioning
confidence: 99%